Naked Exclusion, Efficient Breach, and Downstream Competition - Simpson, John; Wickelgren, Abraham L (American Economic Review, 2007)
Previous papers by Eric B. Rasmusen, J. Mark Ramseyer, and John S. Wiley, Jr. (1991) and Ilya R. Segal and Michael D. Whinston (2000) argue that exclusive contracts can inefficiently deter entry in the presence of scale economies and multiple buyers. We first show that these results no longer hold when buyers are final consumers who can breach these contracts and pay expectation damages. We then show, however, that exclusive contracts can inefficiently deter entry if buyers are downstream competitors, even in the absence of scale economies and even if breach is possible. (JEL D86, K21, L11, L13, L14, L40 )